Cultural and aesthetic influences in the formation of Kelantanese Wayang Kulit characters: a visual analysis - Samsuddin, Mat Redhuan; Nasir, Roziani Mat Nashir @ Mohd; Ahmad, Nani Hartina; Wibowo, Arif Ardy (Faculty of Social and Political Science, Universitas Airlangga, 2025)
Kelantan Wayang Kulit is a traditional art form that embodies the cultural, aesthetic, and symbolic values of the local Malay community. As a form of shadow theatre, it merges narrative, music, and visual aspects, serving as a significant channel for expressing cultural and ethical values. This research seeks to examine the impact of culture and aesthetics on the design development of key characters in Kelantan Wayang Kulit like Seri Rama, Siti Dewi, Maharaja Wana, and Pak Dogol. Employing a qualitative method via visual analysis and semi-structured interviews, this research explores design features like shapes, lines, colors, and motifs that represent the social status, moral values, and cultural identity of the Kelantan community. The results indicate that the character designs are shaped by multiple external factors, including Thai culture and Hindu-Buddhist epics, yet they have been adapted according to local values through dialects, natural motifs, and Malay-Islamic aesthetic principles. Characters like Pak Dogol embody the people’s wisdom through straightforward visual representation. This research highlights that Kelantan Wayang Kulit is more than a cultural heritage; it is also a vibrant and significant medium of visual communication. These results are significant in initiatives to protect and value traditional art, as well as to motivate modern visual art inspired by cultural heritage.